2011
DOI: 10.1002/ps.2108
|View full text |Cite
|
Sign up to set email alerts
|

Innate factors causing differences in gene flow frequency from transgenic rice to different weedy rice biotypes

Abstract: From this study, it is concluded that the likelihood of gene flow between transgenic rice and weedy rice biotypes is primarily determined by floral synchronisation and secondarily influenced by genetic compatibility and some morphological characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Weedy rice is often managed using flooding and/or herbicides and seldom occurs in other crops or in nonagricultural habitats. Pollen-mediated gene flow from rice to weedy rice has been reported (Chen et al, 2004;Shivrain et al, 2007;Tian et al, 2011;Zuo et al, 2011), and herbicide resistance transgenes in cultivated rice are expected to spread to weedy rice within a few seasons of contact (Gressel, 1999;Zuo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Weedy rice is often managed using flooding and/or herbicides and seldom occurs in other crops or in nonagricultural habitats. Pollen-mediated gene flow from rice to weedy rice has been reported (Chen et al, 2004;Shivrain et al, 2007;Tian et al, 2011;Zuo et al, 2011), and herbicide resistance transgenes in cultivated rice are expected to spread to weedy rice within a few seasons of contact (Gressel, 1999;Zuo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Given the important implications of these findings, more sampling and investigation of PA rice are warranted. Outcrossing rates between weedy and cultivated rice in field trials have been found to be low, between 0.03 and 0.25% and between 0 and 6.66% (Shivrain et al ., ; Zuo et al ., ). Traits such as overlap in plant height and flowering time seem to impact that rate (Zuo et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Outcrossing rates between weedy and cultivated rice in field trials have been found to be low, between 0.03 and 0.25% and between 0 and 6.66% (Shivrain et al ., ; Zuo et al ., ). Traits such as overlap in plant height and flowering time seem to impact that rate (Zuo et al ., ). PA rice acting as a potential conduit between weedy and cultivated rice helps explain the high morphological diversity in weedy rice populations in the United States (Shivrain et al ., ,b) despite the low natural hybridisation rate and the absence of wild relatives.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…variable rates depending on flowering synchrony, environmental conditions, WR biotype and CL cultivar [12,13]. The continuous use of IMI herbicides for several seasons selects RWR individuals and may lead to the replacement of susceptible alleles by IMI resistance alleles in the WR population, that is, genetic assimilation [14].…”
mentioning
confidence: 99%